Bereavement and palliative care: A public health perspective - Rumbold, B.; Aoun, Samar (Maney Publishing, 2014)
In recent years there has been an increasing emphasis upon public health perspectives that place palliative care in the context of end-of-life services across whole populations. There is little corresponding public health interest in bereavement. Yet if we have to develop relevant, coherent, and comprehensive end-of-life care policies and practices, public health approaches to palliative care need to be accompanied by public health approaches to bereavement care. We argue here that palliative care services should match their commitment to providing a good death with a commitment to supporting good grief, and that this means investing their efforts principally in developing community capacity for bereavement care rather than seeking to deliver specialized bereavement services to relatives and friends of those who have received palliative care services.